1 - L'Afrique face à l'idéologie de l'EurAfrique: Néo-colonialisme ou panafricanisme ? - Guy MARTIN, (Africa Development, 1982)
This article is an inquiry into the major causes of the continued state of underdevelopment and dependency of Africa in spite of its enor- mous wealth and tremendous economic potential. It argues that one of the main reasons for this situation lies in the nature of the political , economic and cultural ünks which have tied Africa to Europe ever since the fifteenth century . Trade , based on unequal exchange and specilization, constitutes the mainstay of this relationship, be it the slave trade from the fifteenth to the nineteenth centuries , the «trade economy» of the «colonial pact» from 1900 to I960 , or the neo-colonial trade since then . The ideology of Eurafrica , based on the two key concepts of « complementarity » and « interdependence », appears as a convenient justification for colonialism, and also helps to explain various contractual arrangements between Africa and Europe since independence, notably the Conventions of Yaounde I (1964-69), Yaounde II (1969-75), Lomé (1975-80) and Lomé II (1980-85). In the final analysis, this ideology appears as nothing but the rationalization of the neo-classical theory of international development, and of the contemporary international division of labour. Ultimately, of the various alternative strategies, it seems that continental economic and political integration offers the best prospects for extricating Africa from the neo-colonial predicament in which it pre- sently finds itself, and for the attainment of genuine and complete eco- nomic independence.